Historical landscape ecology of an urbanized California valley: wetlands and woodlands in the Santa Clara Valley - Grossinger, Robin M; Striplen, Charles J; Askevold, Ruth A; Brewster, Elise; Beller, Erin E (Landscape ecology, 2007)
Historical records provide information to land managers and landscape ecologists attempting to understand current trajectories in altered landscapes. In this study, we synthesized a heterogeneous array of historical sources to reconstruct historical land cover in California's Santa Clara Valley (a.k.a. “Silicon Valley”). To increase and assess accuracy, we used the triangulation of overlapping, independent data sources and the application of certainty level standards. The region has been subject to extensive urbanization, so we also evaluated the applicability of historical landscape reconstructions to the altered landscape. We found evidence for five major land cover types prior to significant Euro-American modification. Valley freshwater marsh, wet meadow, alkali meadow, willow grove, and valley oak savanna have all experienced extreme decline (85-100%) since Euro-American settlement. However, comparison of historical land cover patterns to contemporary land use suggested several new strategies for environmental recovery, despite the limitations of surrounding urbanization. We also observed a temporal shift in riparian habitat along the mainstem of Coyote Creek, from a relatively open mixture of riparian scrub, sycamore woodland, and unvegetated gravel bars to dense riparian forest, likely resulting from stream flow regulation. By identifying former land cover patterns we provide a basis for evaluating local landscape change and setting restoration targets, including the identification of residual features and under-recognized land cover types. These findings suggest that reliable historical landscape reconstructions can be developed in the absence of standardized historical data sources and can be of value even in highly modified regions.